A hill of beans - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. Chuckwagon trail western., 2020)
"Mac Mackenzie has enough problems on his plate. He's got bounty hunters on his tail, no one on his side, and no place to hide. Just when he thinks it can't get any worse, he hears the rumbling of a cattle stampede--heading straight for his camp. Mac's got two choices: Get trampled like a weed or saddle up and help get the herd under control. At first, the traildrivers ain't too pleased to have a stranger help them out. But once they realize Mac's not a rustler, they ask him to join the team. Mac takes them up on the offer--especially after he meets the cowgirl Colleen--and quickly impresses everyone with his cooking skills. There's just a few more problems: Mac's new employers might be the real rustlers. And Mac's stepped out of the frying pan into the fire..." -- Amazon.